Compost and biochar assisted phytoremediation potentials of Moringa oleifera for remediation of lead contaminated soil. (2018)
The aim of this study was to investigate the germination, growth, tolerance and Pb accumulation potentials of Moringa oleifera in compost and biochar amended Pb-contaminated soils for possible phytoremediation. Lead slag contaminated soil (100%–32,640 mg/kg) was diluted into three Pb contamination levels (75%, 50%, and 25%) by mixing it with uncontaminated control (0%) soil. Sunflower-poultry manure compost (Compost), rice husk biochar (RHB) and groundnut shell biochar (GSB) were applied at 10 g/kg separately to the soils in triplicates and incubated for 2 weeks. Moringa oleifera seedlings were transplanted at two weeks into the incubated soils and set up in greenhouse experiments. Plant height, stem girth, leaf number and biomass were measured at 4 and 8 weeks. Plant roots and shoots were analysed. Moringa oleifera seeds planted in the contaminated and amended contaminated soils failed to germinate. Its seedlings withered off in 100% and 75% but survived in 25% and 50% amended contaminated and control soils. It tolerated Pb contamination up to 8600 mg/kg. The concentrations of Pb in the roots and shoots of the plants at 8 weeks ranged from 930 to 2100 mg/kg and 420–1120 mg/kg respectively for both contamination levels, indicating Pb phytoaccumulation potentials of M. oleifera. Compost and RHB enhanced M. oleifera roots and shoots production. The combination of compost and M. oleifera improved Pb phytoextraction efficiency. The combination of GSB and M. oleifera improved Pb phytostabilisation efficiency. Utilisation of compost, rice RHB and GSB with M. oleifera may be recommended for phytoremediation of Pb-contaminated soil.